2019
DOI: 10.1007/s10592-019-01149-5
|View full text |Cite
|
Sign up to set email alerts
|

More grist for the mill? Species delimitation in the genomic era and its implications for conservation

Abstract: Species delimitation is one of the most contested areas in modern biology, with widespread disagreement about almost every aspect of the definition and implementation of the "species" label. While this debate is intellectually stimulating, it also has real implications for conservation, where its impacts on taxonomic inflation or inertia can mean that specific populations receive adequate conservation measures or are ignored. Recently, the rise of next generation sequencing and phylogenomics has revolutionised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 79 publications
(95 reference statements)
0
85
0
1
Order By: Relevance
“…Species delimitation, and hence the degree of separation between different groups of biological organisms, is a pivotal concept for modern biology, despite the fact that there is no universal agreement about the species concept itself (Stanton et al 2019). The universal species concept proposed by de Queiroz (2007) -i.e., that species represent separately evolving evolutionary lines without any other defining characterspotentially implies the impossibility of taxonomically defining characters at a general scale.…”
Section: Introductionmentioning
confidence: 99%
“…Species delimitation, and hence the degree of separation between different groups of biological organisms, is a pivotal concept for modern biology, despite the fact that there is no universal agreement about the species concept itself (Stanton et al 2019). The universal species concept proposed by de Queiroz (2007) -i.e., that species represent separately evolving evolutionary lines without any other defining characterspotentially implies the impossibility of taxonomically defining characters at a general scale.…”
Section: Introductionmentioning
confidence: 99%
“…The IUCN definition of a species is provided online: ‘A group of interbreeding individuals with common characteristics that produce fertile (capable of reproducing) offspring and which are not able to interbreed with other such groups, that is, a population that is reproductively isolated from others’ (https://www.iucn.org/downloads/en_iucn_glossary_definitions.pdf), which is essentially the BSC. Given discrepancies in defining ‘species’, some scientists have suggested that conservation biology would benefit the most by concentrating on assessing the adaptive potential of evolutionary significant units rather than engage in mental gymnastics about ‘species’ (Fraser & Bernatchez, 2001; Funk, McKay, Hohenlohe, & Allendorf, 2012; Mable, 2019; Stanton et al., 2019).…”
Section: Species Subspecies and Endangered Speciesmentioning
confidence: 99%
“…However, other academic publications question whether the taxonomy adopted by O'Connor et al. (2019) reflects the ‘most in‐depth analysis of genetic evidence’ (Petzold & Hassanin, 2020; Stanton et al., 2019), so the giraffe ‘taxonomic quandary’ (Bercovitch & Deacon, 2015) continues.…”
Section: How Many Species Of Giraffe Are There?mentioning
confidence: 99%
“…It now has a more contemporaneous meaning, defined primarily by population genomic data, and represents a conservation unit isolated demographically from other such units (Mussmann, Douglas, Chafin, & Douglas, 2019; Palsbøll, Bérubé, & Allendorf, 2014). While genomic data clearly hold great potential for elucidating the evolutionary process, arguments must still be resolved before they become a de facto diagnostic tool for species delineation (Stanton et al., 2019). For example, genomic techniques were unsuccessful in unraveling a hybrid complex among Darwin's finches in the Galapagos (Zink & Vázguez‐Miranda, 2019).…”
Section: Introductionmentioning
confidence: 99%